What Difference Does Central Bank Digital Currency Make? Insights from an Agent-based Model - Simon Hess (Universität Rostock, Wirtschafts- und Sozialwissenschaftliche Fakultät, Institut für Volkswirtschaftslehre, 2025)
This paper studies the effects of introducing a Central Bank Digital Currency (CBDC) on economic output, bank intermediation and financial stability in a closed economy using an Agent-based Stock Flow Consistent (AB-SFC) Model. Thereby a digital bank run is simulated across various economic environments with different monetary policy and bank bankruptcy regimes. According to the model, non-remunerated CBDC issued in a positive-interest environment with a corridor system may increase GDP through increased seigniorage income and government spending. Also bank funding becomes more expensive since bank deposit stickiness is prevented. Non-remunerated CBDC issued in a zero-interest environment has no impact since there is no distributional effect of the interest payments. In a floor-system where the interest rate on CBDC matches the policy rate, CBDC also counteracts deposit stickiness and redistributes bank profits from shareholders to depositors. Thereby CBDC improves the transmission of the policy rate to households and firms. The bank bankruptcy regime also affects the outcome. While CBDC makes no difference in a bailout regime it does in a bail-in regime where it decreases inequality and distributes bank rescue costs evenly among households and firms, potentially enhancing financial stability. Introducing CBDC within a deposit insurance system postpones bank rescue payments, which creates an additional dynamic in GDP.
Keywords: E42; E58; G21; G23; G28; 330; central bank digital currency; agent-based model; bank run; bailout; bail-in; financial stability